Strategy Computer Games and Discourses of Geopolitical Order - Rolf F. Nohr (Eludamos, 2010)
This article presents some thoughts on the forms and functions of ‘hidden’ knowledge in popular strategy games. It concentrates specifically on discourses of geopolitical thinking to argue that actual games use and reproduce specific forms of a geographical and political knowledge which are both deeply connected to the ideas of an extreme national and political thinking of the early 20th century, and form a way of describing globalized forms of order, policy and conflict. Exposing this idea will take a three-step approach. First, the close linkage between strategy games and spatial concepts in general needs to be examined. Second, some structural arguments of classical geopolitics of the 1920s to 1960s in contemporary strategy games must be revealed. Finally, this text refers to current booms and renaissances of such geopolitical discourses. In short: this article tries to show how politics are coded as actions in space and how the German “Lebensraum”-policy is connected to Samuel Huntington’s Clash of Civilization via Age of Empires